2001
DOI: 10.1067/mtc.2001.114938
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptor subtype A blockade selectively reduces pulmonary pressure after cardiopulmonary bypass

Abstract: The present study demonstrated that increased activity of the endothelin-1A receptor likely contributes to alterations in pulmonary vascular resistance in the postbypass setting. Selective endothelin-1A blockade may provide a means to selectively decrease pulmonary vascular resistance without significant effects on systemic hemodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…A larger, prospective study will be necessary to directly address this issue. Consistent with past reports,24,25,34,35 plasma ET levels increased significantly in the post-CPB period, and is likely due increased synthesis and spillover from interstitial compartments such as the myocardium 33,34. In the ET-ARA groups, plasma ET levels were increased to the greatest degree in the post-CPB period.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A larger, prospective study will be necessary to directly address this issue. Consistent with past reports,24,25,34,35 plasma ET levels increased significantly in the post-CPB period, and is likely due increased synthesis and spillover from interstitial compartments such as the myocardium 33,34. In the ET-ARA groups, plasma ET levels were increased to the greatest degree in the post-CPB period.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, oral formulations of both non-selective and ET-A subtype selective antagonists have been described to be efficacious in pulmonary hypertension16,18,22 However, an oral formulation of an ET-ARA would not be of practical clinical use in an acute care setting, and therefore infusible formulations of selective ET-ARAs would be required. This laboratory has described previously basic and clinical studies using an intravenous formulation of the ET-ARA, sitaxsentan 24,25,35. These past studies demonstrated a significant reduction in pulmonary vascular resistance following post-CPB 25,35.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While mechanistic links remain to be established, ET release and cytokine activation have been associated with a protracted post operative course following CPB [69]. Past studies have demonstrated that ET has diverse biological effects on myocyte contractility and upon the vasculature [1012]. The cardiovascular effects of ET are mediated through two unique receptor subtypes: ET-A receptor (ET-AR) and ET-B receptor (ET-BR).…”
Section: Introductionmentioning
confidence: 99%
“…The cardiovascular effects of ET are mediated through two unique receptor subtypes: ET-A receptor (ET-AR) and ET-B receptor (ET-BR). ET-AR mediates local and systemic vasoconstriction and has negative inotropic effects [1012]. In contradistinction, ET-BR mediates the release of vasodilatory factors, such as nitric oxide, as well as facilitates ET clearance [13, 14].…”
Section: Introductionmentioning
confidence: 99%